Exposure to Al2O3 nanoparticles facilitates conjugative transfer of antibiotic resistance genes from Escherichia coli to Streptomyces. Issue 10 (26th November 2019) - Liu, Xiaomei; Tang, Jingchun; Song, Benru; Zhen, Meinan; Wang, Lan; Giesy, John P.
Abstract: The spread of antibiotic resistance genes (ARGs) has become a global environmental issue; it has been found that nanoparticles (NPs) can promote the transfer of ARGs between bacteria. However, it remains unclear whether NPs can affect this kind of conjugation in Streptomyces, which mainly conjugate with other bacteria via spores. In the present study, we demonstrated that Al2 O3 NPs significantly promote the conjugative transfer of ARGs from Escherichia coli ( E. coli ) ET12567 to Streptomyces coelicolor ( S. coelicolor ) M145 without the use of heat shock method. The number of transconjugants induced by Al2 O3 particles was associated with the size and concentration of Al2 O3 particles, exposure time, and the ratio of E. coli and spores. When nanoparticle size was 30 nm at a concentration of 10 mg/L, the conjugation efficiency reached a peak value of 182 cfu/10 8 spores, which was more than 60-fold higher than that of the control. Compared with nanomaterials, bulk particles exhibited no significant effect on conjugation efficiency. We also explored the mechanisms by which NPs promote conjugative transfer. After the addition of NPs, the intracellular ROS content increased and the expression of the classical porin gene ompC was stimulated. In addition, ROS enhanced the mRNA expression levels of conjugative genes by inhibiting global regulation genes. Meanwhile, expression of the conjugation-related gene intA was also stimulated, ultimately increasing the number of transconjugants. Our results indicated that Al2 O3 NPs significantly promoted the conjugative transfer of ARGs from bacteria to spores and aggravated the diffusion of resistance genes in the environment.